Test and measurements [1999 technology analysis and forecast]. - Masi, C.G (IEEE spectrum)
This article presents a test and measurements technology analysis and forecast for 1999. The subject covered include network instruments, virtual testers, measurement automation, data security and PC-based next-generation instruments